PENGEMBANGAN PROFESIONALISME GURU SEKOLAH DASAR MELALUI KELOMPOK KERJA GURU (KKG) - Hendrizal; Nadra Yanti; Resti Yuliana; Ade Yatma; Trio Malta (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to explore and analyze the development of teacher professionalism at the elementary school level through the implementation of Teacher Working Groups (KKG). Teacher professionalism has a significant impact on the quality of education and student development. KKG is considered an effective strategy in improving the competence and quality of teacher work. This research method uses a qualitative approach with a case study research design. Data was collected through in-depth interviews with teachers, classroom observations, and analysis of documents related to the KKG. The research results show that KKG has an important role in developing teacher professionalism in elementary schools. In the context of KKG, teachers can share their experiences, knowledge and best practices. Regular discussions in KKG help teachers to identify and resolve problems they may face in teaching. In addition, the KKG also provides opportunities to access additional educational resources and necessary training. Implementation of the KKG helps improve the quality of learning in the classroom, while strengthening the teacher community in elementary schools. Teachers feel more motivated and connected to their colleagues, which in turn improves their professional well-being. Thus, this research provides a better understanding of the role of KKG in improving teacher professionalism at the elementary school level.